A large-scale phylogeny of Amphibia including over 2800 species, and a revised classification of extant frogs, salamanders, and caecilians - Alexander Pyron, R.; Wiens, John J. (Molecular phylogenetics and evolution, 2011)
[Display omitted] ► Large-scale molecular phylogenetic estimate for Amphibia. ► Based on 2871 species: 41 caecilians, 436 salamanders, and 2394 frogs. ► Species sampled for up to 12,712 bp from nine nuclear and three mitochondrial genes. The extant amphibians are one of the most diverse radiations of terrestrial vertebrates (>6800 species). Despite much recent focus on their conservation, diversification, and systematics, no previous phylogeny for the group has contained more than 522 species. However, numerous studies with limited taxon sampling have generated large amounts of partially overlapping sequence data for many species. Here, we combine these data and produce a novel estimate of extant amphibian phylogeny, containing 2871 species (∼40% of the known extant species) from 432 genera (∼85% of the ∼500 currently recognized extant genera). Each sampled species contains up to 12,712 bp from 12 genes (three mitochondrial, nine nuclear), with an average of 2563 bp per species. This data set provides strong support for many groups recognized in previous studies, but it also suggests non-monophyly for several currently recognized families, particularly in hyloid frogs (e.g., Ceratophryidae, Cycloramphidae, Leptodactylidae, Strabomantidae). To correct these and other problems, we provide a revised classification of extant amphibians for taxa traditionally delimited at the family and subfamily levels. This new taxonomy includes several families not recognized in current classifications (e.g., Alsodidae, Batrachylidae, Rhinodermatidae, Odontophrynidae, Telmatobiidae), but which are strongly supported and important for avoiding non-monophyly of current families. Finally, this study provides further evidence that the supermatrix approach provides an effective strategy for inferring large-scale phylogenies using the combined results of previous studies, despite many taxa having extensive missing data.